Market structure and innovations in automotive industry: hybrid and electric cars - Souza, Kellen Rocha de (Departamento de Economia, 2015)
Since the car was invented many innovations have been developed; these, however, have been more concerned with increasing speed, power of the motor and weight of the car than with the reduction of fuel consumption. The result is that the auto industry has been classified by the authors as Abramovay (2012) and Lovins, Lovins e Hawken (2013) as an inefficient industry. Moreover, given the consequences generated by the significant increase of greenhouse gas emissions, massive traffic jams, something that until one time was observed only in large cities, among other, the development of technologies that reduce fuel consumption is of great importance. In this respect, the current emphasis is the technology of hybrid and electric cars. In this research beyond the discussion about the “inefficiency” of the automobile industry and hybrid and electric cars, the goal is also to analyze the degree of concentration in the Brazilian automobile market. The results of the concentration ratio (CR3 and CR4) and the Herfindahl-Hirschman Index (HHI) indicated a high concentration of the market, despite the reduction in inequality between firms.